Investigation and Enhancement Using Different Types of Pipelines for the Servo Hydraulic System with PID Controller Tuned Using Fuzzy Logic - Shaymaa M. Mahdi (مجلة النهرين للعلوم الهندسية, 2017)
This paper aims to investigate the effect of using different types of pipelines with the servo hydraulic system enhanced with PID controllers tuned by fuzzy logic. The mathematical models of several types of pipelines with different specifications (i.e. area variations in the pipe, disturbance source, etc.) are developed. The effect of the modified pipelines on the position control system at spool displacement is tested,since the servo hydraulic systems are difficult to control due to nonlinearity and complexity of their mathematical models. A  PID controller tuned using fuzzy logic technique is used to improve the servo hydraulic system response.The results show that the mathematical models of the pipelines have a significant effect on the performance of the position control system at spool displacement according to the used pipeline type.Furthermore, a more desirable time response specifications and less steady state error are achieved after using the proposed controller.